2016
DOI: 10.2196/ijmr.5668
|View full text |Cite
|
Sign up to set email alerts
|

Media Use by Children, and Parents’ Views on Children's Media Usage

Abstract: BackgroundNew (mobile phones, smartphones, tablets, and social media) and traditional media (television) have come to dominate the lives of many children and adolescents. Despite all of this media time and new technology, many parents seem to have few rules regarding the use of media by their children and adolescents.ObjectivesThe aim of this study was to evaluate media access/use of children and to evaluate beliefs and attitudes of parents concerning the use of old and new media in Turkey.MethodsThis is a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 21 publications
(43 reference statements)
5
33
1
Order By: Relevance
“…Children who did not have consistent adult supervision were more likely to use screen for more than 1 hour and had signi cant delays in attention, social skills, and intelligence. Mealtime use of screen was much higher in our population (72.5%) than reported literature (22-50%) [14,15], and it had a negative effect on the duration of screen use.…”
Section: Resultscontrasting
confidence: 67%
“…Children who did not have consistent adult supervision were more likely to use screen for more than 1 hour and had signi cant delays in attention, social skills, and intelligence. Mealtime use of screen was much higher in our population (72.5%) than reported literature (22-50%) [14,15], and it had a negative effect on the duration of screen use.…”
Section: Resultscontrasting
confidence: 67%
“…Another study from Korea suggested similar findings [10]. The screen time is significantly more in this study as compared to other previous studies probably because they are having country-specific guidelines regarding daily screen time and general awareness [11][12][13]. In addition, possession of smart phones by most of the parents grants easy access for the children to the devices [7].…”
Section: Discussionsupporting
confidence: 72%
“…Many researchers have reported associations between early media exposure and outcomes as wide ranging as sleep ( Cheung et al, 2017 ), obesity ( Jackson et al, 2009 ), antisocial behavior ( Zimmerman and Christakis, 2007 ), attention problems ( Christakis et al, 2004 ), and language delays ( Zimmerman et al, 2007 ). Higher screen time has been identified as a key predictor of poorer outcomes in many nations, including Turkey ( Dinleyici et al, 2016 ), Canada ( Madigan et al, 2019 ), and Hong Kong ( Fu et al, 2017 ) and in a recent series of qualitative studies across seven European countries ( Chaudron, 2015 ). Despite multiple studies reporting negative associations between media use and child outcomes, mixed findings abound.…”
Section: Introductionmentioning
confidence: 99%